Procurement Outsourcing Strategies and Organizational Agility: A Comparative Analysis of Pharmaceutical Companies in Brazil - Ribeiro, Vanessa (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to analyze the procurement outsourcing strategies and organizational agility: a comparative analysis of pharmaceutical companies in Brazil. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on procurement outsourcing and organizational agility in Brazilian pharmaceutical firms found that comprehensive outsourcing boosted agility through external expertise, streamlining processes and improving cost-effectiveness. In contrast, reliance on in-house procurement posed challenges to adaptability and competitiveness. Strategic procurement outsourcing emerged as vital for enhancing organizational agility in Brazil's pharmaceutical industry. Unique Contribution to Theory, Practice and Policy: Resource-Based View (RBV), transaction cost economics (TCE) & dynamic capability theory may be used to anchor future studies on analyze procurement outsourcing strategies and organizational agility: a comparative analysis of pharmaceutical companies in Brazil. Pharmaceutical companies in Brazil should develop customized procurement strategies that align with their unique internal resources, capabilities, and strategic objectives. Policymakers should encourage collaboration between pharmaceutical companies and outsourcing partners by providing regulatory support and incentives.